First and Ten: A Fresh Look at the Cleveland Browns - McKee, Vince (Rowman & Littlefield Publishers, 2023)
A celebration of the greatest moments in recent history for the Cleveland Browns Cleveland is a blue-collar city with hardworking people that support their hardworking teams. No matter the previous seasons’ records, Cleveland’s loyal fan base always returns. And no matter the amount of losses, dysfunction, or controversy, the Cleveland Browns remain one of the most popular franchises in professional football. In First and Ten: A Fresh Look at the Cleveland Browns, Vince McKee covers the new history of the Browns after their return to the NFL in 1999, including several winning seasons and numerous runs toward the playoffs. From a Hail Mary touchdown pass by Tim Couch to secure the first victory of the new era to a playoff victory led by Baker Mayfield over the Pittsburgh Steelers, this book captures it all. And while McKee focuses on the positive moments and impactful players, he doesn’t shy away from reflecting on the negatives when necessary, providing a fresh look at this storied franchise. First and Ten covers all the fun—and sometimes the chaos—of this beloved team. It’s a tale for every Browns fan who wears their orange and brown proudly, every week, no matter the team’s record.